2015
DOI: 10.1016/j.apgeochem.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Uranium fate in Hanford sediment altered by simulated acid waste solutions

Abstract: Infiltration of aqueous acidic waste to the subsurface may induce conditions that alter contaminant transport. Experiments were conducted to examine the effects of low pore water pH and associated changes to sediment properties on U(VI) behavior in sediments. Macroscopic batch experiments were combined with a variety of bulk characterization studies (Mössbauer and laser spectroscopy), micron-scale inspections (µ-XRF), and molecular scale interrogations (XANES) with the objectives to: 1) determine the extent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The ferrous iron produced from dissolution reactions could reduce uranium, if adsorbed to iron oxide surfaces (Liger et al 1999) resulting in U(IV) precipitates, although adsorption of ferrous iron would only occur once the acidic conditions were pH buffered to greater than pH 6. However, there were no significant differences in uranium sorption/precipitation response for batch experiments under acidic conditions that were conducted under atmospheric conditions compared to those in a controlled atmosphere with no measureable oxygen and carbon dioxide (Gartman et al 2014). These data suggest that reductive processes induced by acid neutralization of the tested Hanford Site sediments are not a significant contributor to overall uranium partitioning to solids at low pH.…”
Section: Uranium and Non-uranium Precipitatesmentioning
confidence: 75%
See 3 more Smart Citations
“…The ferrous iron produced from dissolution reactions could reduce uranium, if adsorbed to iron oxide surfaces (Liger et al 1999) resulting in U(IV) precipitates, although adsorption of ferrous iron would only occur once the acidic conditions were pH buffered to greater than pH 6. However, there were no significant differences in uranium sorption/precipitation response for batch experiments under acidic conditions that were conducted under atmospheric conditions compared to those in a controlled atmosphere with no measureable oxygen and carbon dioxide (Gartman et al 2014). These data suggest that reductive processes induced by acid neutralization of the tested Hanford Site sediments are not a significant contributor to overall uranium partitioning to solids at low pH.…”
Section: Uranium and Non-uranium Precipitatesmentioning
confidence: 75%
“…Sorption experiments demonstrated that uranium behavior in regions of the subsurface with low pH (e.g., pH 2) shows increasing sorption of uranium to the solid phase with large increases in ionic strength and sodium nitrate concentration (i.e., 1M sodium nitrate increased to 8 M sodium nitrate) (Gartman et al 2014). This behavior would be transient and occur during disposal, likely only in zones where the neutralization capacity became exhausted.…”
Section: Uranium Sorption and Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…A com pa ra ble con clu sion was drawn by Mishra [33], who in ves ti gated the sorp tion be hav ior of ura nium in ag ri cul tural soils. Gartman et al [34] stud ied U(VI) fate in Hanford sed i ment and found that sed i ment sorp tion fit the Freundlich iso therm in the ab sence of air ex per i ments.…”
Section: ( )mentioning
confidence: 99%